Continuity of Safety and Lifesaving Training at Sea in Facing Emergency Situations on Board the MT. Jayne-I Owned by PT. Bumi Shipping - Putro, Roy Wahyu Nugroho Adi; Firdaus, Muhammad Imam; Rahayu, Trisnowati; Suwondo, I'ie (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Safety and lifesaving at sea are vital in ship operations, particularly on tankers facing high risks of fires, explosions, collisions, and sinking. To mitigate these risks, implementing continuous safety training per international regulations is crucial. This study aims to evaluate and establish the continuity of safety and lifesaving training on the MT. Jayne-I tanker (owned by PT. Bumi Shipping), aligning it with international standards like SOLAS 1974. This study utilized a qualitative descriptive method. Data was collected through direct onboard observation, crew interviews, and the examination of ship safety documents, including muster lists and emergency procedures. Results indicate that while safety and lifesaving training on the MT. Jayne-I is conducted routinely, it remains suboptimal. Key obstacles include the crew's low awareness regarding the importance of safety training, inadequate proficiency with safety equipment, and a tendency for exercises to be formalistic rather than simulating actual emergencies. Additionally, the ship's demanding operational schedule negatively impacts training continuity. In conclusion, improving the effectiveness and continuity of safety training on the MT. Jayne-I is essential. This requires highly disciplined, meticulously planned exercises adhering strictly to SOLAS 1974, STCW 1978, and the ISM Code. By enhancing training quality, the crew will be better prepared and skilled in handling emergencies, ultimately ensuring the safety of lives, the vessel, its cargo, and the marine environment.